2020
DOI: 10.1002/art.41195
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP‐Ribose) Polymerase Enhances Infiltration of Mononuclear Cells in Primary Sjögren's Syndrome Through Interferon‐Induced Protein With Tetratricopeptide Repeats 1–Mediated Up‐Regulation of CXCL10

Abstract: Objective Mononuclear cell infiltration and type I interferon (IFN) system activation play an important role in primary Sjögren's syndrome (SS). We undertook this study to investigate the mechanism of poly(ADP‐ribose) polymerase family member 9 (PARP‐9) on mononuclear cell infiltration triggered by type I IFN. Methods A proteomic study was conducted in peripheral blood mononuclear cells from patients with primary SS (n = 30) and healthy controls (n = 30) to determine differentially expressed proteins (DEPs) (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The increase of CXCL10 mRNA was slower than those of IFIT1, IFIT2, and IFIT3 and reached maximum 16 h after the poly IC treatment. It has been reported that overexpression of IFIT1 upregulated CXCL10 expression in B cells [26]. In the present study, knockdown of IFIT1, IFIT2, or IFIT3 resulted in the decrease of CXCL10 expression induced by poly IC, suggesting that IFIT1, IFIT2, and IFIT3 positively regulate the expression of CXCL10 in GECs.…”
Section: Discussionsupporting
confidence: 66%
“…The increase of CXCL10 mRNA was slower than those of IFIT1, IFIT2, and IFIT3 and reached maximum 16 h after the poly IC treatment. It has been reported that overexpression of IFIT1 upregulated CXCL10 expression in B cells [26]. In the present study, knockdown of IFIT1, IFIT2, or IFIT3 resulted in the decrease of CXCL10 expression induced by poly IC, suggesting that IFIT1, IFIT2, and IFIT3 positively regulate the expression of CXCL10 in GECs.…”
Section: Discussionsupporting
confidence: 66%
“…It consequently promotes the downstream gene expression of the Notch signaling pathway and ultimately accelerates the angiogenesis of endothelial cells ( Wang et al, 2020a ). In primary Sjogren’s syndrome, the DTX3L/BAL1 complex enhances the phosphorylation of STAT1 to upregulate IFN-induced protein with tetratricopeptide repeats 1 (IFIT-1) and increases the expression of chemokine (C–X–C motif) ligand 10 (CXCL10), thereby promoting the infiltration of mononuclear cells ( Tian et al, 2020 ).…”
Section: Functions and Associated Molecular Mechanisms Of The Dtx Familymentioning
confidence: 99%
“…MS4A1 has also been identified in a study published by Luo et al (15). CD19+ B cells are often used for the identification of pSS and have been widely verified as a diagnostic marker (61,62). CCL19 maybe involved in more sever forms of autoimmune diseases, such as rheumatoid arthritis (63).…”
Section: Discussionmentioning
confidence: 95%